MIH - EPIDEMIOLOGICAL STUDY ON A SAMPLE FROM PAEDODONTICS DEPARTMENT - Mihaela Tănase; Ioana-Andreea Stanciu; Aneta Munteanu; Daciana Zmărăndache; Cătălina Farcaşiu; Rodica Luca (Amaltea Medical Publishing House, 2018)
Objectives. To assess the distribution, topography and severity of MIH lesions as well as the associated carious in a group of children examined at the Pedodontics Department, Bucharest. Material and method. Retrospective descriptive observational study performed on dental records of 100 patients (38 boys) (6-12 years) diagnosed with MIH. The distribution, topography and severity of MIH defects, as well as associated decay were recorded. There were calculated: the number of patients with MIH/MH, the average number of first permanent molars (M1p)/permanent incisors (I) with MIH/patient, the distribution of M1p/I affected according to the topography and severity of the defects, the mean number of M1p with MIH and associated caries/ patient. Statistical analysis was performed with SPSS 18.0 using ANOVA and t-test (p<0.05). Results. Patients with MIH = 52%, patients with MH = 48%. Girls (62%) were statistically significantly more affected than boys (38%)(p<0.05). Mean number of affected M1p/patient=3.66 and mean number of affected I/patient=1.24. The most interested were 46 (95%) and 11(56.66%). 69.67% of M1p with MIH had hypomineralization in occlusal third (20.21% at the top of the cusps, 13.66% at the bottom of the cusps and 35.79% on all occlusal third) and 7.92% in the medium third. 26.8% of M1p with MIH had mild defects, 46.4% moderate defects, 26.8% severe defects. The mean M1p with MIH and associated decay/patient=2.7: 52.18% with uncomplicated caries and 21.31% with complicated caries. Conclusions. The severity of MIH in the studied group is high; It is necessary to early diagnose MIH lesions in order to prevent further complications.